Ukrainian detective (Soviet and emigre): History and pragmatics (1920-1930). RETRACTED 21.03.2025: RETRACTED 21.03.2025 - Zubko, Olga (V. N. Karazin Kharkiv National University Bulletin History of Ukraine. Ukrainian Studies: Historical and Philosophical Sciences, 2024)
The task of scientific research. The study of ukrainian soviet and emigration literary tastes, which changed under the pressure of historical realities in the 1920s and 1930s. Distinguishing the concepts of «ukrainian soviet detective story» and «ukrainian emigration sensational stories». Methodology of research and scientific approaches. Methodology of research is based on the principles of historicism, objectivity, comprehensiveness, integrity, systematicity, as well as on the use of methods of analysis and synthesis, historical‑genetic, historical-comparative, historically-typological, problem-chronological. The main results of the research carried out within the article. It was found out that the soviet detective by Volodymyr Vynnychenko, Dmytro Buzko, Georgy Danylovych, and Yuri Smolych prevailed in the 1920s. There were many autobiographical allusions in the storylines of the soviet detective. The Vynnychenko novel «Gold Deposits» sparked interest due to the mysterious fraudulent schemes of the characters, which reflected the corruption of the Directory period. In the story «Lyolya» by Dmytro Buzko, the author’s repatriation and his undisguised desire to settle scores with those involved in the «supruniada» it was read. «Provocateur» by Georgy Danylovych was the first attempt in such a literary genre as a classic detective story. Yuri Smolych intrigued with espionage (the detective story «One and a Half Men») and fiction (the detective story «The Household of Doctor Galvanescu»). In the 1930s, party ideologistses cunning bullet targeted the soviet ukrainian detective, which caused a lot of trouble for Yuri Shovkoplyas with his doctor Piddubny, because there could not possibly be any maniacs, rapists, or thieves of socialist property or any criminal domestic plots in a soviet detective story. Instead, the 1930s were the years of emigration sensational novels. At that time, Ukrainian immigrants on the European continent enjoyed reading the works of Hryhoriy Luzhytskyi, who «did not invent the bicycle», but continued to promote the glorious Ukrainian past, adding new Ukrainian heroes to it – the most ordinary emigrants, fighters, detectives. Among his sensational stories, the most famous are: «The First Night» (1928), «Comrades of the Smile» (1929), «The Room with One Entrance» (1931), «The Clock with the Broken Glass» (1933), «Shot in the Night» (1934), «Hallo!..Hallo!..Attack on the bank!» (1935); trilogy «Crimson Cross» (1931 - 1937). Originality and practical significance. Reading books by ukrainians as a psychological release and relief from stressful situations on both sides of the border during the period between the two world wars is the clear example of practicality and intellectual satisfaction, which is so important in our time. Prospects for studying the problem. The study of the literary preferences of ukrainian soviet readers and ukrainian emigrants in the 1920s and 1930s as recreation is promising from the perspective of such a scientific direction as everyday history, which examines the conditions of life, work and rest, as well as factors affecting the formation of consciousness and norms of behaviour , socio-political preferences, etc. of the vast majority of the population («ordinary people», «nameless», «silent») of one or another country in one or another historical period.